2021
DOI: 10.1186/s12913-021-06457-6
|View full text |Cite
|
Sign up to set email alerts
|

Could existing infrastructure for using patient‐reported outcomes as quality measures also be used for individual care in patients with colorectal cancer?

Abstract: Background There has been increasing interest in integrating patient-reported outcomes (PROs) into routine oncological practice. To date, however, PROs have rarely been implemented in Germany. Currently, PROs are being used as performance measures in colorectal cancer centers in Germany. This content analysis identified factors that may inhibit or facilitate the additional use of PROMs for individual patient management. Methods The analysis follows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Of the total 17 papers, 8 introduced a study in which study participants had used only ePROs [21][22][23][24][25][26][27][28]. In the other 9 papers [29][30][31][32][33][34][35][36][37], only some of the participants had used ePROs, while others had used nondigital PROMs. The ePRO systems used were AmbuFlex [21,26], OncoQuest [22], Noona [23], the KLIK method [25], and PatientViewpoint [28].…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the total 17 papers, 8 introduced a study in which study participants had used only ePROs [21][22][23][24][25][26][27][28]. In the other 9 papers [29][30][31][32][33][34][35][36][37], only some of the participants had used ePROs, while others had used nondigital PROMs. The ePRO systems used were AmbuFlex [21,26], OncoQuest [22], Noona [23], the KLIK method [25], and PatientViewpoint [28].…”
Section: Overviewmentioning
confidence: 99%
“…The most frequently used PROM was the Edmonton Symptom Assessment Scale (ESAS) [32][33][34]. Studies were carried out in multiple countries: the Netherlands [22,25,31], Germany [27,29], the United Kingdom [24], the United States [23,28,35,37], Denmark [21,26], Canada [32,34], Australia [33] Laitio et al JMIR CANCER…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research is underway to evaluate the applicability and benefits and harms of collecting PROMs in routine clinical care. 10 Future research should focus on investigating the feasibility of prompt feedback of patient‐reported data to clinicians and incorporating the results of patient‐reported measures into clinical practice.…”
Section: Recommendationsmentioning
confidence: 99%